Ex-PALM: a negative pressure ventilation system for air leak evaluation in ex vivo lungs - Vartazarmian, Mark; Abid, Alexandre; Chermat, Rodin; Têtu, Maxime; Bulgarelli Maqueda, Luciano; Sarshoghi, Arman; Naghieh, Saman; Périé, Delphine; Liberman, Moishe (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionProlonged air leaks (PAL) are considered to be one of the leading causes of postoperative complications following lung surgery. There are currently no clinically relevant methods for efficiently and systematically evaluating the underlying causes of PAL. Here, we introduce a new intuitive, physiologically-representative system for ex vivo negative pressure ventilation of lungs, equipped with PAL-oriented features.MethodsReproducibility and system capabilities were assessed using a lung simulation model capable of controlling the effective area of the defect, then validated with ex vivo specimens.ResultsOur system enables dynamic control of ventilation using either pressure (PCV) or volume (VCV) targets, with respective standard deviations of ±0.08 cm H2O and ±2.1 mL with moderate air leaks (<1,000 mL/min) and respective standard deviations of ±0.18 cm H2O and ±11 mL with severe air leaks (>1,000 mL/min). Additionally, leak quantification features proved comparable to that of the Thopaz+ (Medela Healthcare, Baar, Switzerland), a standard commercial digital thoracic drainage system, offering sufficient resolution to differentiate among clinically relevant air leaks. In the lower leak ranges (<400 mL/min) across all methods of evaluations, there were no significant differences between measured leak rates. For higher leak ranges, although there remained no significant differences between the Ex-PALM methods evaluated, the Thopaz + proved to systematically report lower leak rates values (Thopaz+ 420.0 ± 10.0 mL/min vs. PCV-derived 449.0 ± 19.9 mL/min, p < 0.05) and (Thopaz+ 1,200.0 + 0.0 mL/min vs. PCV-derived 1,239.7 ± 21.1 mL/min, p < 0.001). Unlike current systems, coughing was predictably replicated using peak pressure targets ranging from 100 to 300 cm H2O with a standard deviation of ±1.30 cm H2O from target. Our system allows extraction of biomechanical parameters at every breath, with theoretically expected pressures matching experimental measurements with a goodness fit value (R2) above 0.95 for the vast majority of breaths.DiscussionThe Ex vivo Pulmonary Air Leak Model (Ex-PALM) provides a preclinical PAL testing platform with high translational potential and applications in studying biomechanical mechanisms of PAL and developing intraoperative mitigation strategies.